2017
DOI: 10.1111/ijfs.13466
|View full text |Cite
|
Sign up to set email alerts
|

Heated or raw Blue cheeses: what are the drivers influencing consumer preferences?

Abstract: Six French Blue cheeses (two cheese types of varying ripening times) were evaluated under two treatment conditions, raw cheeses (without heating) and heated cheeses (with heating), in order to describe the sensory properties of raw and heated cheeses and to identify the sensory keys drivers of liking and disliking that explain consumer preference patterns. A trained panel performed sensory profiles of selected cheeses. In parallel, 153 French consumers evaluated the same cheeses for overall liking and intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Conversely, there is evidence that bitterness is not a desirable cheese characteristic for some consumers, as reported by several authors (Arcia, Curutchet, Costell, & Tarrega, ; Bord, Guerinon, & Lebecque, ; Caspia et al, ; Young, Drake, Lopetcharat, & McDaniel, ; Zhang et al, ). A dislike for “bitter” taste has also been studied in other food products than cheese, such as whole‐grain products (Bakke & Vickers, ), extra virgin olive oils (Barbieri et al, ; Delgado & Guinard, ; Recchia, Monteleone, & Tourila, ) or green vegetables (Chadwick, Gawthrop, Michelmore, Wagstaff, & Methven, ; Dinnella et al, ; Poelman, Delahunty, & Graaf, ).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Conversely, there is evidence that bitterness is not a desirable cheese characteristic for some consumers, as reported by several authors (Arcia, Curutchet, Costell, & Tarrega, ; Bord, Guerinon, & Lebecque, ; Caspia et al, ; Young, Drake, Lopetcharat, & McDaniel, ; Zhang et al, ). A dislike for “bitter” taste has also been studied in other food products than cheese, such as whole‐grain products (Bakke & Vickers, ), extra virgin olive oils (Barbieri et al, ; Delgado & Guinard, ; Recchia, Monteleone, & Tourila, ) or green vegetables (Chadwick, Gawthrop, Michelmore, Wagstaff, & Methven, ; Dinnella et al, ; Poelman, Delahunty, & Graaf, ).…”
Section: Resultsmentioning
confidence: 86%
“…Other authors, has also determined that flavor was more a driving force in overall liking of different cheeses (raw milk cheeses) than texture (Liggett, Drake, & Delwiche, ; Yates & Drake, ; Young et al, ). However, in a study on PDO Blue‐veined cheese, Bord et al () found that texture characteristics were the key sensory drivers of liking for 48.4% of consumers. So, the influence of the texture on the consumers' preferences could also be influenced by the kind of cheese.…”
Section: Resultsmentioning
confidence: 99%
“…The same design was used to select cheese samples as previously described by Bord et al (). French PDO blue cheeses were chosen, and more specifically Fourme d'Ambert cheese, made with cow's milk from the Auvergne region of France.…”
Section: Methodsmentioning
confidence: 99%
“…French PDO blue cheeses were chosen, and more specifically Fourme d'Ambert cheese, made with cow's milk from the Auvergne region of France. Two types of cheese (SA and SB) having different sensory features but made by the same dairy company were selected, differing only in the ratio of fermented cocktail content, with a starter culture and Penicillium roqueforti (Bord et al, ). All the cheeses were made from pasteurized milk based on the same industrial cheese‐making process (fat standardization, maturation of milk, coagulation, stirring, draining, and pricking of curd).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation